PRODUCTION OF BIOETHANOL FROM DIFFERENT PLANT SOURCES - kuriakose, Telphy (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Bio fuels from various sources such as Jatrophacurcas, Pongamiapinnata, Azadirachtaindica, Madhucaindica etc are produced till now. Ethanol is made biologically from cellulosic biomass, and using substrates such as molasses, fruit pulps and peels etc. are well known. Since the need of bioethanol has been increasing, in this study we used peels of citrus, non-citrus fruits, Pseudo stem of banana as substrates, due to its cheaper, ecofriendly and whole year availability. A chemical pre-treatment process using acid hydrolysis was applied. The amount of carbohydrate and alcohol was determined before and after the pretreatment. Cellulose degrading bacteria isolated from the midgut of the earthworms was inoculated into the pretreated samples, fermenting the substrate for alcohol production. Ethanol production in culture samples was determined by spectroscopic method. Results indicate that ethanol can be made from fruit peel residue and that the acid hydrolysis was effective in removal of lignin, which acts as physical barrier to cellulolytic enzymes and causes the release of 20%-30% more sugar.